Metamaterials: Flexible and Transparent Microwave–Infrared Bistealth Structure (Adv. Mater. Technol. 8/2019). Issue 8 (8th August 2019) - Zhang, Changlei; Wu, Xiaoyu; Huang, Cheng; Peng, Jinqiang; Ji, Chen; Yang, Jianing; Huang, Yijia; Guo, Yinghui; Luo, Xiangang
Abstract : A flexible and transparent microwave‐infrared bi‐stealth structure is presented. As described in article number1900063 by Xiangang Luo and co‐workers, the elaborately designed metamaterial keeps optical transparency and flexibility due to the use of indium tin oxide (ITO) films and polyvinyl chloride (PVC) substrates. By combining the intrinsic material properties with proper design, the proposed metamaterial can simultaneously achieve high absorption in the microwave band and high reflectivity in the infrared band. These interesting properties at the optical, microwave, and infrared bands are represented by the three electromagnetic wave beams in this image.